AN ANALYSIS OF GENDER DIFFERENCES IN LANGUAGE LEARNING STRATEGIES OF ELF STUDENTS - Ni Wayan Juniari; Luh Putu Artini; Ni Luh Putu Eka Sulistia Dewi (Jurnal Ilmiah Spectral, 2023)
TThis study aims to analyze the influence of gender differences between men and women in language learning strategies in the process of learning English for undergraduate students of English Education. This research uses the qualitative analysis technique for information collection. The information analysis of this study is the authors review the same three studies. Research findings indicate that students use a wider range of learning strategies that differ from those often preferred by their gender. Each women and men often use social strategies whereas the bottom frequency strategies differently. The research result helpful for language academics of increasing their awareness to reduce the gap between students' language learning strategies and their preference of teaching techniques.